The components of national identity and their defense according to Abdelhamid Ben Badis (مجلة إحالات, 2026)
This research paper focuses on the components of national identity and their concepts accordingto Abdelhamid Ben Badis. He viewed identity as a set of stable, diverse connections and sought torestore the Algerian nation by reviving its character through various reforms.Ben Badis was a reformer and a leader in the Algerian struggle against French colonialism, whichaimed to erase Algerian national identity. This paper will outline the national components of theAlgerian people as defined by Ben Badis, including Islam, the Arabic language, and the homeland,along with his reformist and activist journey to defend these elements and inspire the Algerian people to reclaim their sovereignty and identity.